A Bibliometric Analysis of Generation Z and Tourism Research: Insights from VOSviewer Mapping - Ioana-Simona Ivasciuc; Adina Nicoleta Candrea; Ana Ispas; Brenda-Andreea Piuaru (Administrative Sciences)
In recent years, Generation Z has had a pivotal influence across global industries, with tourism being significantly impacted. As the first generation fully immersed in digital technology, Generation Z members have travel preferences, behaviours, and values which differ markedly from previous generations, presenting both challenges and opportunities for the tourism sector. This study explores studies on Generation Z in the context of the tourism industry through key research questions, including the primary trends and thematic clusters in the existing literature, the most influential journals and authors, and the temporal evolution of research in this area. To address these questions, this article presents a comprehensive bibliometric analysis of 217 publications on Generation Z and tourism, spanning from 2018 to 2024, sourced from the Web of Science. Using VOSviewer, the analysis maps the main trends, the most influential publications, and the emerging themes, providing insights into how Generation Z is reshaping the tourism landscape. The bibliometric analysis and VOSviewer mapping add a rigorous methodological approach, offering a structured overview of existing research while identifying gaps for further exploration, especially in this emerging field. The study highlights the most published and cited journals, providing a broad contextual view, followed by an in-depth exploration of thematic clusters within Generation Z tourism research. The results indicate that although research on this topic gained attention in 2018, it is still in its early stages, with significant room for expansion. Current studies primarily focus on social media marketing communications for Generation Z, as well as Generation Z tourism experiences and their attitudes and preferences towards tourism, suggesting areas for future exploration.